The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1097/sih.0000000000000479
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Simulation to Identify Latent Safety Threats During Neonatal Magnetic Resonance Imaging Procedure

Abstract: Introduction: Transfer of infants for magnetic resonance imaging (MRI) from the neonatal intensive care unit (NICU) requires exposure to unfamiliar environments and involve multiple complex human and system interactions, which can compromise patient safety. In situ simulation (ISS) offers an opportunity to identify latent safety threats (LSTs) that may occur during this high-risk procedure. Our primary aim was to use ISS to identify modifiable LSTs during the MRI procedure: involving neonatal transport to/from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
1
0
2
Order By: Relevance
“…ISS has also been used to identify and reduce risks during the transport of neonatal patients. One study even promoted changes in transport policy for imaging exams 111 . Another study showed an improvement in general performance and teamwork in orotracheal intubation in trauma care 43 .…”
Section: Thematic Area Total Participantsmentioning
confidence: 99%
“…ISS has also been used to identify and reduce risks during the transport of neonatal patients. One study even promoted changes in transport policy for imaging exams 111 . Another study showed an improvement in general performance and teamwork in orotracheal intubation in trauma care 43 .…”
Section: Thematic Area Total Participantsmentioning
confidence: 99%
“…A SIS também foi utilizada para identificar e reduzir riscos durante o transporte de pacientes neonatais. Um estudo promoveu, inclusive, mudanças na política de transporte para realização de exames de imagem 111 . Outro estudo mostrou a melhora do desempenho geral e do trabalho em equipe na intubação orotraqueal, no atendimento ao traumatizado 43 .…”
Section: Evidências Associadas àS Habilidades Não Técnicas Dos Profis...unclassified
“…A SIS também foi utilizada para identificar e reduzir riscos durante o transporte de pacientes neonatais. Um estudo promoveu, inclusive, mudanças na política de transporte para realização de exames de imagem (WONG et al, 2021). Outro estudo mostrou a melhora do desempenho geral e trabalho em equipe na intubação orotraqueal e atendimento ao traumatizado (AUERBACH et al, 2014).…”
Section: Simulação In Situunclassified